1997
DOI: 10.1007/bf03189816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of two nifedipine products in capsule form following single oral administration in healthy volunteers

Abstract: The pharmacokinetic parameters (AUC, Cmax, Tmax, and t1/2) of nifedipine following single oral administration of a 10 mg capsule of test product were compared to those of the same amount of a reference product. The two products in capsule form were administered according to a randomized two-way crossover design in 22 healthy male volunteers. Nifedipine plasma concentrations were determined using a rapid, sensitive and precise high performance liquid chromatography (HPLC) method with ultraviolet (UV) detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…Mean pharmacokinetic parameters for both nifedipine and free silibinin observed in the present study are similar to those reported in the literature [9], [26], [27], [28], [29]. Specifically, silibinin exposure with C max values of up to 0.4 mM was in the expected range [9].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Mean pharmacokinetic parameters for both nifedipine and free silibinin observed in the present study are similar to those reported in the literature [9], [26], [27], [28], [29]. Specifically, silibinin exposure with C max values of up to 0.4 mM was in the expected range [9].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, intraindividual variability of nifedipine pharmacokinetics was higher than reported. Multiplicative coefficients of variation below 17 % and 30 % for the AUC and Cmax, respectively, were expected [26], [27]. The intraindividual CV found here for AUC was 25 %, that for C max reached 120 %.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, the severity of the pathology of the PH between the two studies is different. Second, amlodipine has a longer half‐life 28,29 than nifedipine 30 (3.08 ± 1.61 vs 0.93–01.12 h, respectively). Both these factors may contribute to the differences in the effects between nifedipine and amlodipine in attenuating PH 28 …”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous publications describing the determination of nifedipine concentrations in plasma or serum such as HPLC–UV and electrochemical detection , SPE on cyano cartridges with HPLC–UV , and GC–MS . Also, different methods for the quantification of AMB have been reported which include TLC , GC with various detection methods and HPLC–UV , LC–MS/MS , and fluorimetry detection .…”
Section: Introductionmentioning
confidence: 99%